Myo-Cortical Crossed Feedback Reorganizes Primate Motor Cortex Output - Lucas, Timothy H. (Society for Neuroscience, 2013)
The motor system is capable of adapting to changed conditions such as amputations or lesions by reorganizing cortical representations of peripheral musculature. To investigate the underlying mechanisms we induced targeted reorganization of motor output effects by establishing an artificial recurrent connection between a forelimb muscle and an unrelated site in the primary motor cortex (M1) of macaques. A head-fixed computer transformed forelimb electromyographic activity into proportional subthreshold intracortical microstimulation (ICMS) during hours of unrestrained volitional behavior. This conditioning paradigm stimulated the cortical site for a particular muscle in proportion to activation of another muscle and induced robust site- and input-specific reorganization of M1 output effects. Reorganization was observed within 25 min and could be maintained with intermittent conditioning for successive days. Control stimulation that was independent of muscle activity, termed “pseudoconditioning,” failed to produce reorganization. Preconditioning output effects were gradually restored during volitional behaviors following the end of conditioning. The ease of changing the relationship between cortical sites and associated muscle responses suggests that under normal conditions these relations are maintained through physiological feedback loops. These findings demonstrate that motor cortex outputs may be reorganized in a targeted and sustainable manner through artificial afferent feedback triggered from controllable and readily recorded muscle activity. Such cortical reorganization has implications for therapeutic treatment of neurological injuries.